2008
DOI: 10.1002/jcla.20250
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ciguatoxin in fish tissue using sandwich ELISA and neuroblastoma cell bioassay

Abstract: The applicability of a new enzyme-linked immunoassay (ELISA) for detecting ciguatoxin (CTX) in fish tissue was evaluated by testing three fish species commonly implicated in ciguatera fish poisoning in Hawaii. A total of 164 individual almaco jack (Seriola rivoliana) and greater amberjack (S. dumerili) and a total of 175 individuals of the blue-spotted grouper (Cephalopholis argus) were caught at various locations in the Hawaiian Islands. Muscle tissue from each individual was assessed for the presence of CTX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Differences between the ELISA and NB assay results imply that 2.1% of results are false positives when assessing the aquacultured fish using the ELISA alone, and show that 1.2% of results are false positives when screening the wild-caught kahala compared to the NB results. In addition, the wild kahala data (Table 2) imply that 1.7% of results are false negatives, confirming a previous study which indicated that 1.2% of results were considered false negatives when using the ELISA (Campora et al 2008b).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Differences between the ELISA and NB assay results imply that 2.1% of results are false positives when assessing the aquacultured fish using the ELISA alone, and show that 1.2% of results are false positives when screening the wild-caught kahala compared to the NB results. In addition, the wild kahala data (Table 2) imply that 1.7% of results are false negatives, confirming a previous study which indicated that 1.2% of results were considered false negatives when using the ELISA (Campora et al 2008b).…”
Section: Discussionsupporting
confidence: 84%
“…As a tool for CTX screening, the ELISA shows promise for its capabilities of efficiently and economically screening a large number of fish samples using a unique two-site antibody configuration. However, cross-reactivity of extraneous lipids and the establishment of a somewhat arbitrary positive threshold may inadvertently score fish as positive or borderline that are truly negative, leading to an overall estimated 2.7% false-positive rate when using the ELISA (Campora et al 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…The specific Neuroblastoma cell assay methodology followed Campora et al (2008). In short, the presence of ciguatoxin in muscle tissue was determined by comparing the survival rate of neuroblastoma cells in treatment wells containing fish extract with that in control wells without extract, with lowered survival in treatment wells indicating cytotoxicity.…”
Section: Validation Of Membrane Immunobead Assay Results With the Neumentioning
confidence: 99%
“…Antibodies have been prepared for CTX and used in different formats over the years including immunobead assay, radioimmunoassay, or ELISA (Hokama et al, 1990(Hokama et al, , 1998Campora et al, 2008), yet the accuracy of the results has been questioned (Dickey et al, 1994;Lehane and Lewis, 2000;EFSA, 2009a;Bienfang et al, 2011). Monoclonal antibodies specific to Pacific ciguatoxins CTX-3C and 51-hydroxyCTX3C (Tsumuraya et al, 2006) have been prepared using synthetic haptens and used to develop a sandwich ELISA.…”
Section: Biological Methodsmentioning
confidence: 99%